Predatory activity of Chrysoperla externa (Neuroptera: Chrysopidae) on Macrosiphum euphorbiae (Hemiptera: Aphididae) in Rosa sp. Crop. (2016)
The objectives of this study was to assess the efficiency of third instar larvae of Chrysoperla externa and to quantify its population control on different densities of Macrosiphum euphorbiae aphids on greenhouse rose crops. For 24 hours, the consumption of C. externa on first and second stage nymphs of M. euphorbiae at a predator: prey ratio of 1:10 was evaluated on four different aphid densities. In the second stage, the predatory capacity of C. externa was compared over a period of 31 days on four (40, 80, 120, 160) initial densities of M. euphorbiae, through the weekly release of predator larvae at a predator: prey ratio of 1:10. This experiment showed that C. externa has a greater predatory capacity at higher M. euphorbiae densities. It was also observed that the initial density of aphids did not influence the consumption of C. externa larvae over a 31 day observation period. However the predator kept the population of M. euphorbiae at lower densities on plants where C. externa larvae were released. Nevertheless, the number and frequency of larvae released did not provide complete aphid population control.